(untitled) (Palíndromo, 2018)
In this article, we will take an approach on the place of performance in the circuit of contemporary art. To accomplish that, we will reflect on the work of Tony Camar-go, visual artist and performer who stresses the limits imposed on performance art by capturing and editing photographs of his plays. When we look at the Fotomódulosseries, we try to understand how and when, for him, the performance record becomes a work of art. The artist was interviewed with the intention of understanding which layers are superimposed on his performance in the production and post-production of the photographs that capture his gestures. We do not pretend to develop a critical analysis of the formal quality of his work, but rather to map the procedures that makes possible, for Tony, to capture the performative ges-ture as a museum artefact. From Auslander (2013) and Agra (2009), we will articulate the tensions imposed on the documenta-tion of the performance, seen by some as another form of art.